Oral hygiene practices in nurseries (0-3 years) in the cities of Pavia and Vigevano - Marzia Segù; Laura Baroni; Federica Bertuzzi; Camilla Preda (Frontiers Media S.A., 2023)
AimThis study was conducted to evaluate attention to and knowledge of oral care in children aged 0-3 years, on the basis of data collected from early years educators working with this age group. Information was also collected about the oral hygiene practices adopted in nurseries and the types of food provided, with the aim of increasing knowledge and raising awareness of this topic.Materials and methodsA questionnaire was created using the "Google Forms" program and sent to all the 47 nurseries in the city of Pavia and Vigevano.ResultsTwenty establishments agreed to take part in the research. Assessment of knowledge and of awareness of oral care among early years educators caring for children in the age range 0-3 years revealed variability and some confusion. The results showed a general lack of attention to oral care in the period before the milk teeth appear, as well as limited use of gauze swabs. There was generally some use of educational play focusing on this issue, albeit not daily across all the nurseries participating in the survey. Nurseries rarely had the support of a professional dental hygienist to raise awareness among early years educators and parents.ConclusionsThe findings obtained through this study indicate that, in the area surveyed, there is a lack of widespread knowledge and awareness of oral prevention in young children, and of the oral hygiene maintenance techniques to use in this age group. This suggests a need to develop preventive protocols to improve knowledge and awareness of children's oral health among the adults who care for them.